The identity of the offender as an element of forensic characteristics of premeditated murder of a hostage or a kidnapped person - V. V. Kikinchuk; T. V. Bilyk (Law and Safety)
Scientific research and forensic practice on the identity of the offender who committed the premeditated murder of a hostage or a kidnapped person are analyzed. The content of such a criminal person’s typology in the system of forensic characteristics of crimes against human life and health is revealed. A review of modern definitions is made, the essence and concept of the person of the criminal who committed premeditated murder of the hostage or kidnapped person is analyzed, as well as its main features are analyzed and the typology of the person of the criminal who committed premeditated murder of the hostage or kidnapped person is developed.